2008
DOI: 10.1093/toxsci/kfn158
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, Morphological, and Biochemical Changes after In Ovo Exposure to Methylmercury in Chicks

Abstract: Methylmercury (MeHg) is an environmental pollutant known to induce neurotoxicity in several animal species, including humans. However, studies focusing the effects of MeHg poisoning in chicks were based on phenomenological approaches and did not delve into the molecular mechanisms. The purpose of this study was to evaluate the postnatal consequences of the in ovo exposure to MeHg on behavioral, morphological and biochemical parameters in chicks. At the fifth embryonic day (E5), Gallus domesticus eggs were subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
3
27
0
6
Order By: Relevance
“…This effect, which is probably related to the higher nucleophilicity and softness of selenols when compared to thiols, reinforces the idea that the selenium-mercury interaction possesses an important role in the neurotoxicity induced by MeHg. In agreement with the foregoing data on MeHg and GPx, thioredoxin reductase (TrxR), another important antioxidant selenoprotein, has also been reported to be a molecular target involved in MeHg toxicity (Carvalho et al 2008; 2011; Wagner et al, 2010). Based on both in vivo and in vitro experiments, the authors propose that MeHg can bind to selenocysteine residues present in the catalytic site of TrxR, thus causing enzyme inhibition that can compromise the redox state of cells.…”
Section: Mehg Interacts With Selenol Groupssupporting
confidence: 70%
See 1 more Smart Citation
“…This effect, which is probably related to the higher nucleophilicity and softness of selenols when compared to thiols, reinforces the idea that the selenium-mercury interaction possesses an important role in the neurotoxicity induced by MeHg. In agreement with the foregoing data on MeHg and GPx, thioredoxin reductase (TrxR), another important antioxidant selenoprotein, has also been reported to be a molecular target involved in MeHg toxicity (Carvalho et al 2008; 2011; Wagner et al, 2010). Based on both in vivo and in vitro experiments, the authors propose that MeHg can bind to selenocysteine residues present in the catalytic site of TrxR, thus causing enzyme inhibition that can compromise the redox state of cells.…”
Section: Mehg Interacts With Selenol Groupssupporting
confidence: 70%
“…Such symptoms were also observed in experimental studies using cats (Charbonneau et al, 1976), dogs (Mattsson et al, 1981), mice (Inouye et al, 1985; Dietrich et al, 2004); rats (Rocha et al, 1993; Farina et al, 2005), monkeys (Rice, 1996) and zebrafish ( Danio rerio ) (Samson et al, 2001). Although experimental studies on MeHg-exposed animals have shown that behaviors related to visual (visual contrast sensitivity task; Burbacher et al, 2005), cognitive (passive avoidance task; Ferraro et al, 2009) and emotional (depression-like behavior evaluated in the forced swimming test; Onishchenko et al, 2007) functions are also affected by MeHg exposures, movement disorders , consisting mainly of ataxia and loss of balance, have been extensively reported in experimental studies using MeHg-exposed animals (Dietrich et al, 2004, Farina et al, 2005; Lucena et al, 2007) and have been used as an important behavioral parameter to correlate with histological/cellular damage and/or biochemical changes (Franco et al, 2006; Carvalho et al, 2007, Carvalho et al, 2008), as well as to study potential protective/antidotal strategies to counteract MeHg-induced toxicity (Farina et al, 2005; Martins et al, 2009). …”
Section: Behavioral Hallmarksmentioning
confidence: 99%
“…AQP11 is expressed in the Purkinje cells of the brain cerebellar [1], a site that have been implicated in the pathophysiology of autism [36,37]. Exposure of chick embryo to the environmental metal pollutant methylmercury led to reduction in the number of Purkinje cells [38]. Furthermore, there were adverse post-natal behavioral, morphological and biochemical consequences.…”
Section: Discussionmentioning
confidence: 99%
“…We are currently studying the specificity and affinity of a range of cations to further understand the interaction of cations with aquaporins in the function of the central nervous system. With the availability of the chicken genome, the chick embryo has the potential to serve as an important model for the study of the development of neurodegenerative disorders [38,41]. …”
Section: Discussionmentioning
confidence: 99%
“…A galinha nasce com uma capacidade funcional muito grande, principalmente se comparada aos mamíferos. Mesmo assim, a diversidade e eficiência de comportamentos aumentam bastante no período pós-natal (Carvalho et al, 2008). Entre P0 e P16, observamos um grande aumento na expressão de Cx43.…”
Section: A Cx43 E a Formação Das Sinapses Do Córtex Cerebelarunclassified